Hyperparathyroidism with a giant parathyroid tumour with capsular infiltration - De Mel, W.C.P.; Casinader, M.; Wijesiriwardena, B.C.; Sheriffdeen, A.H.; Sheriff, M.H.R. (College of General Practitioners of. Sri Lanka, 1983)
We present the case of a 39 year old lady with primary hyperparathyroidism who had been suffering from a multitude of symptoms and marked psychiatric manifestations for a period of 2 years. She had an unusually large parathyroid tumour which showed evidence of capsular infiltration on histological examination. She was treated surgically and has remained well in the past 1 year.
Sri Lankan Family Physician: 1983; Vol: 6; 69-71p.